Islamic Character Education within the Merdeka Curriculum Framework: A Case Study of MAN 4 Denanyar - Fifin Izzatul Maulidiya; Didin Sirojudin (LPPM Universitas KH. A. Wahab Hasbullah, Jombang, Indonesia, 2025)
This study aims to explain the formation of Islamic character through the independent curriculum at MAN 4 Denanyar Jombang. The focus of research includes 2 main aspects, namely: (1) The application of the independent curriculum through the formation of Islamic character in MAN 4 Denanyar Jombang, and (2) Problematic and Merdeka Curriculum Solutions to the Formation of Islamic Characters in MAN 4 Denanyar Jombang. This study uses a qualitative deskrptive approach, with data collection techniques in the form of in -depth interviews, observations, and documentation. This method is ideal for understanding the background of the problem, individual social interaction, or studying groups as a whole, with case study research as the first choice in qualitative research. The results of the study explained that: (1) the application of an independent curriculum through the formation of Islamic character in MAN 4 Denanyar Jombang by planning to hold a Bullying and Early Marriage Prevention Seminar, then the implementation of Islamic character formation through the independent curriculum is contained in the RPP and through the Intracuricular, Ceocular and Extracurricular, and finally instilling religious values and discipline and then slipping Islamic values in each material theme; To evaluate the formation of Islamic character through an independent curriculum, namely through assessment and report cards. (2) Problematics and solutions to form Islamic character through the Merdeka Curriculum in MAN 4 Denanyar Jombang, namely there are supporting factors through teachers, students, infrastructure, environmental conditions and behavior approaches. Then there is an inhibiting factor that is lack of understanding so that it cannot impose technology. Then for the solution by frequently holding meetings, training, training and workshops. This research makes a practical contribution to teachers and policy makers in developing Islamic character formation through an independent curriculum in madrasas and providing insights on the implementation of an independent curriculum in the local context